2018
DOI: 10.7181/acfs.2018.02264
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of nasal bone fracture

Abstract: BackgroundNasal bone fractures occur frequently because the nasal bone is located at the forefront of the face. The goal of this study was to examine the cause, change in severity, change in incidence, and demographics of nasal bone fracture according to today’s lifestyle.MethodsA total of 2,092 patients diagnosed as having nasal bone fractures at our department between 2002 and 2017 were included in this study. We retrospectively examined patients’ medical records to extract information regarding age, sex, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
0
13
0
4
Order By: Relevance
“…Rhinoplasty is needed to correct these irregularities which will increase the cost of the patient and needs open surgical procedure. 1,9 With a successful initial reduction of the deformity, post op complication can be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Rhinoplasty is needed to correct these irregularities which will increase the cost of the patient and needs open surgical procedure. 1,9 With a successful initial reduction of the deformity, post op complication can be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Closed reduction is the standard surgical method for nasal bone fractures [1][2][3][4], which are the most common fracture of the facial bones. Kaukola et al [7] evaluated the quality of life of patients undergoing reduction due to zygomatic fractures and investigated the symptoms of patients who continued to complain of discomfort even months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal bone fractures, which are the most common type of facial bone fractures [1][2][3][4][5], often result in structural or functional complications. Surgical results vary depending on the type of nasal bone fracture and/or the presence of septal fracture or deviation, even after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Common causes include assault, fall, and traffic accidents. 7 Previous studies showed that in 46.9% of nasal bone fractures have concomitant septal fracture. 8 The senior author (Y. D.) previously described three types of septal fracture patterns including isolated cartilaginous, single fracture through the osseocartilaginous junction, and multiple fractures at any location occurring at progressively higher amounts of force.…”
Section: Fracture Patternsmentioning
confidence: 99%
“…Of 45 patients who underwent open rhinoplasty within 4 weeks of fracture, spreader grafts and extracorporeal septoplasty were used predominantly in different fracture patterns, with a revision rate of 4.4%. 7 Proponents of acute septorhinoplasty approach stress that direct visualization of the nasal bones allows for more accurate reduction. In the Asian population, patients may request dorsal augmentation concurrently, and this can be addressed safely at the time of nasal fracture reduction per Kim et al 34 Challenges include fibrosis and difficult dissection of fractured nasal bone segments.…”
Section: Open Septorhinoplasty In Acute Traumamentioning
confidence: 99%